1998
DOI: 10.1016/s0014-5793(98)00709-1
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin metabolites inhibit copper ion‐induced lipid peroxidation in rat plasma1

Abstract: The oxidative susceptibility of plasma obtained from rats after intragastric administration of quercetin was studied to know whether or not quercetin acts as an in vivo antioxidant after metabolic conversion. Quercetin was raised in the rat blood plasma essentially as glucuronide and/or sulfate conjugates. The plasma obtained from rats after quercetin administration was more resistant against copper sulfate-induced lipid peroxidation than the control plasma on the basis of the accumulation of cholesteryl ester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
3
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(105 citation statements)
references
References 22 publications
3
96
3
3
Order By: Relevance
“…This conclusion appears premature in the light of the fact that quercetin undergoes avid metabolism in species that may possess pharmacological activity, as hinted by our finding that isorhamnetin and tamarixetin are potent COX-2 inhibitors, at least in cells in vitro. Consistent with the notion that quercetin metabolites may be partially responsible for the pharmacological activity of the parent flavonol, quercetin conjugates have previously been found to retain, at least in part, the abilities of the parent molecule to exert antioxidation (Da Silva et al, 1998;Manach et al, 1998) and to inhibit xanthine oxidase and lipoxygenase (Day et al, 2000). Furthermore, products of the metabolic fission of quercetin have been shown to demonstrate greater antioxidant potency than their precursor (Merfort et al, 1996).…”
Section: Discussionmentioning
confidence: 60%
“…This conclusion appears premature in the light of the fact that quercetin undergoes avid metabolism in species that may possess pharmacological activity, as hinted by our finding that isorhamnetin and tamarixetin are potent COX-2 inhibitors, at least in cells in vitro. Consistent with the notion that quercetin metabolites may be partially responsible for the pharmacological activity of the parent flavonol, quercetin conjugates have previously been found to retain, at least in part, the abilities of the parent molecule to exert antioxidation (Da Silva et al, 1998;Manach et al, 1998) and to inhibit xanthine oxidase and lipoxygenase (Day et al, 2000). Furthermore, products of the metabolic fission of quercetin have been shown to demonstrate greater antioxidant potency than their precursor (Merfort et al, 1996).…”
Section: Discussionmentioning
confidence: 60%
“…Circulating metabolites of flavonoids, such as glucuronides, sulphates and conjugated O-methylated forms, or intracellular metabolites like flavonoid-GSH adducts, have greatly reduced antioxidant potential [160]. Indeed, studies have indicated that although such conjugates and metabolites may participate directly in plasma antioxidant reactions and in scavenging reactive oxygen and nitrogen species in the circulation, their effectiveness is reduced relative to their parent aglycones [41,122,152,170,189].…”
Section: Flavonoid Metabolism and Access To The Brainmentioning
confidence: 99%
“…Flavonoids are polyphenols and, therefore, considered to be metabolized mainly as conjugated derivatives by coupling with a glucuronic acid or a sulfuric acid during the phase II biotransformation pathway in vertebrates. There have been several reports [3][4][5][6] on the conjugative metabolism of flavonoids, particularly quercetin which is one of the most widely distributed flavonoids found in fruits and vegetables. 7,8) The conjugation of quercetin is somewhat complicated since it also undergoes methylation of its catechol moiety on the B-ring in addition to glucurono-and sulfo-conjugation in the body.…”
mentioning
confidence: 99%
“…Quercetin metabolites are found as glucurono-or sulfo-conjugates of quercetin and isorhamnetin, a 3Ј-O-methylated form of quercetin, in the plasma of rats and humans administered quercetin. [3][4][5][6] However, details of the different glucurono-and sulfo-conjugated forms of quercetin and isorhamnetin are still poorly understood. In the present studies, the metabolism of kaempferol lacking one of the ortho-dihydroxyl substitutions on the Bring of quercetin was investigated using rat liver subcellular preparations and cultured hepatocytes.…”
mentioning
confidence: 99%